The effect of erythropoietin on biomechanical properties of the Achilles tendon during the healing process: an experimental study. Issue 1 (December 2016) - Bilal, Okkes; Guney, Ahmet; Kalender, Ali; Kafadar, Ibrahim; Yildirim, Muzaffer; Dundar, Nuh
Abstract Background The aim of this study was to examine the potential biomechanical and histological benefits of systemic erythropoietin administration during the healing of Achilles tendon injury in a rat experimental model. Methods Eighty Sprague-Dawley female rats were included in this study. Animals were randomly assigned into two groups with 40 animals in each: erythropoietin group and control group. Then each group was further divided into four subgroups corresponding to four time points with 10 animals in each. A full-thickness cut was made on the Achilles tendon of each animal and then the tendon was sutured with modified Kessler method. Erythropoietin groups received intraperitoneal erythropoietin (500 IU/kg/day) every day at same time throughout the study period, and the control groups received saline in a similar manner. Animals were sacrificed at four time points, and tensile test was performed on each tendon sample to assess maximum load for each sample. In addition, histopathological examination and scoring was done. Results Both groups had improvement on tensile test (maximum load) over time. However, groups did not differ with regard to maximum load in any of the time points. Similarly, groups did not differ with regard to any of the histopathological scores over time. Conclusions The findings of this study do not support the benefit of systemic erythropoietin administration in Achilles tendon healing process. Further evidence from larger experimental studies is required to justify any such potential benefit.